DESKRIPSI MOTORIK KASAR SISWA KELAS ATAS SEKOLAH DASAR DAERAH PERBUKITAN - Maria Goreti Wati; Touvan Juni Samodra; Edi Purnomo; Eka Supriatna; Uray Gustian; Davi Sofyan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this study is related to the importance of gross motor skills in elementary school students, especially students who live in hilly areas. Gross motor is a movement of the whole body that involves large muscles such as crawling, walking, running, jumping, and throwing. This research was conducted at the 38 Nanga Tayap Public School, Ketapang Regency. The sample in the study of upper-class students (grades 4, 5, and 6) was 44 students. Data collection was taken from May 18 to May 20, 2022. Data collection was carried out using a gross motor ability test, namely TGMD-2 (run, gallop, hop, horizontal jump, leap, slide, striking). A stationary ball, stationary dribble, catch, kick, overhand throw, or underhand roll). The results showed no superior and excellent, 4.5% above the average, 47.8.% average, 22.7% below the average and 22.7% less, and 2.3 % significantly less. So it can be concluded that more than 50% of class students still have gross motor skills below the standard average